(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The development of export activities in the textile industry is an important factor in ensuring economic growth, increasing foreign exchange revenues, and strengthening the competitiveness of national economies. In recent years, Uzbekistan has implemented a number of economic reforms aimed at supporting export-oriented industries, particularly the textile sector. This article examines the economic mechanisms that contribute to the development of export activities of textile industry enterprises and analyzes their functional characteristics using the example of Uzbekistan. The study identifies key economic mechanisms such as financial incentives, tax benefits, investment support, export infrastructure development, and institutional regulation. Special attention is given to the role of government policies and industrial modernization in increasing export capacity. The findings indicate that effective economic mechanisms can significantly improve the competitiveness of textile enterprises and expand their participation in international markets. The article also provides recommendations for further improvement of export support policies in Uzbekistan.